Model Autoregressive Integrated Moving Average (ARIMA) untuk Peramalan Curah Hujan di Kota Surabaya - Yonlib Weldri Arnold Nanlohy; Gabriella Haumahu (Department of Mathematics, Faculty of Mathematics and Natural Sciences, Pattimura University, Ambon, Indonesia, 2021)
Surabaya is the largest city in the province of East Java and is also the center of the provincial government. In the city of Surabaya the dry season is from May to October and the rainy season is from November to April. Heavy rain usually occurs between December and January. One of the negative impacts caused by excessive rainfall in the city of Surabaya is flooding. The method is often used to predict rainfall in the city of Surabaya, it is Autoregressive Integrated Moving Average (ARIMA). ARIMA models is forecasting model analysis data of single time series or univariate models. The purpose of this study is to forecast the daily rainfall in the city of Surabaya with a ARIMA model